Nonlinear methods in econometrics - Goldfeld, Stephen M.; Quandt, Richard E. (Amsterdam : North-Holland Pub. Co., 1972)
This series consists of a number of unpublished studies, which are introduced by the editors in the belief that they represent fresh contributions to economic science. The term "economic analysis" as used in the title of the series has been adopted because it covers both the activities of the theoretical economist and the research worker.
Includes index.
rpm 12/09/2017
Loans
Keywords: Econometrics